2005
DOI: 10.1111/j.1398-9995.2005.00738.x
|View full text |Cite
|
Sign up to set email alerts
|

IgE, IgG1, and IgG4 antibody responses to Blomia tropicalis in atopic patients

Abstract: A large percentage of our allergic patients are B. tropicalis+. They are more frequently sensitized to high-molecular weight (HMW) B. tropicalis components than the major low-molecular weight (11-15 kDa) allergens detected in other studies. The results suggest that HMW B. tropicalis antigenic components are potential candidates for evaluating allergen exposure and sensitization, and for immunotherapy treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 15 publications
7
38
1
4
Order By: Relevance
“…These results were similar to those of our previous studies carried out in another group of AR patients from the same region (8), confirming that the high rate of this concurrent sensitization has certainly complicated the evaluation of the role of B. tropicalis in these patients, particularly in tropical and subtropical regions where both mites coexist.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These results were similar to those of our previous studies carried out in another group of AR patients from the same region (8), confirming that the high rate of this concurrent sensitization has certainly complicated the evaluation of the role of B. tropicalis in these patients, particularly in tropical and subtropical regions where both mites coexist.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, we demonstrated that there was an important IgE cross-reactivity with the Dp extract even when using the Bt-Con-A extract, suggesting that high-molecular weight allergens could also be involved in this cross-reactivity. Accordingly, in our previous studies (8), AR patients appeared to be preferentially sensi-tized to B. tropicalis high-molecular weight allergenic components as compared to lowmolecular weight allergens. Immunoblotting inhibition studies should be performed using the Bt-total and Bt-Con-A extracts to better characterize the components that are crossreactive and non-cross-reactive with Dp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations